Establishing the cascade of care for hepatitis C in England-benchmarking to monitor impact of direct acting antivirals - Simmons, Ruth; Ireland, Georgina; Irving, Will; Hickman, Matthew; Sabin, Caroline; Ijaz, Samreen; Ramsay, Mary; Lattimore, Sam; Mandal, Sema (Wiley, 2017)
Little is known about engagement and retention in care of people diagnosed with chronic hepatitis C (HCV) in England. Establishing a cascade of care informs targeted interventions for improving case-finding, referral, treatment uptake and retention in care. Using data from the Sentinel Surveillance of Blood Borne Virus testing (SSBBV) between 2005-2014 we investigate the continuum of care of those tested for HCV in England. Persons ≥1 years old, with an anti-HCV test and subsequent RNA tests between 2005-2014 reported to SSBBV were collated. We describe the cascade of care, as the patient pathway from a diagnostic test, referral into care, treatment, and patient outcomes. Between 2005-2014, 2,390,507 samples were tested for anti-HCV, corresponding to 1,766,515 persons. 53,038 persons (35,190 men and 17,165 women) anti-HCV positive were newly reported to SSBBV. An RNA test, was conducted on 77.0% persons anti-HCV positive, 72.3% of whom were viraemic (RNA positive) during this time period, 21.4% had evidence of treatment, and 3130 49.5% had evidence of a sustained virological response (SVR). In multivariable models confirmation of viraemia by RNA test varied by age and region/test setting; evidence of treatment varied by age, year of test and region/test setting; and SVR varied by age, year of test and region/setting of test. In conclusion, Our findings provide HCV cascade of care estimates prior to the introduction of direct acting antivirals. These findings provide important baseline cascade estimates to benchmark progress towards elimination of HCV as a major public health threat.